PoRVA G9P[23] and G5P[7] infections differentially promote PEDV replication by reprogramming glutamine metabolism. - Haixin Liu; Haolun Tian; Pengcheng Hao; Huimin Du; Kun Wang; Yudong Qiu; Xiangrui Yin; Nana Wu; Qian Du; Dewen Tong; Yong Huang (PLoS Pathogens, 2024)
PoRVA and PEDV coinfections are extremely common in clinical practice. Although coinfections of PoRVA and PEDV are known to result in increased mortality, the underlying mechanism remains unknown. Here, we found that PoRVA infection promoted PEDV infection in vivo and in vitro and that PoRVA G9P[23] (RVA-HNNY strain) enhanced PEDV replication more significantly than did PoRVA G5P[7] (RVA-SXXA strain). Metabolomic analysis revealed that RVA-HNNY more efficiently induced an increase in the intracellular glutamine content in porcine small intestinal epithelial cells than did RVA-SXXA, which more markedly promoted ATP production to facilitate PEDV replication, whereas glutamine deprivation abrogated the effect of PoRVA infection on promoting PEDV replication. Further studies showed that PoRVA infection promoted glutamine uptake by upregulating the expression of the glutamine transporter protein SLC1A5. In SLC1A5 knockout cells, PoRVA infection neither elevated intracellular glutamine nor promoted PEDV replication. During PoRVA infection, the activity and protein expression levels of glutamine catabolism-related enzymes (GLS1 and GLUD1) were also significantly increased promoting ATP production through glutamine anaplerosis into the TCA cycle. Consistent with that, siRNAs or inhibitors of GLS1 and GLUD1 significantly inhibited the promotion of PEDV replication by PoRVA. Notably, RVA-HNNY infection more markedly promoted SLC1A5, GLS1 and GLUD1 expression to more significantly increase the uptake and catabolism of glutamine than RVA-SXXA infection. Collectively, our findings illuminate a novel mechanism by which PoRVA infection promotes PEDV infection and reveal that the modulation of glutamine uptake is key for the different efficiencies of PoRVA G9P[23] and PoRVA G5P[7] in promoting PEDV replication.